Преимагинальные фазы развития трех видов подрода вестиплекс - Vestiplex Bezzi (Diptera, Tipulidae) с высокогорий Тянь-Шаня - Второв, П.П.; Савченко, Е.Н. (Вестник зоологии, 1968)
The descriptions and ecological characteristics are given of larvae and pupae of Tipula (Vestiplex) leucoprocta Mik, T. (V.) kashkarovi Stack. and T. (V.) virgatula montivaga S a v. according to the materials from Terskei-Ala-Too (the basin of Chon-Kyzyl-Su river). Their larvae are clearly distinguished from those of boreal species of the subgenus by the absence of dark sclerites on the posterior surface of lateral lobes of the spiracular disk. They also differ one from another by the character of sclerotizalion of dorsal lobes and by development degree of ventral and paraanal lobes (Fig. I, 3 and 5). In the pupae of the group the specific features are less pronounced (Fig. 2, 4 and 6). In the series T. leucoprocta—T. kashkarovi — T. virgatula montivaga the sclero-tization intensity of dorsal lobes of the spriracular disk as well as the progressing reduction of the ventral and paraanal lobes attends the growing xeraphilous ability of th: larvae which is also observed in other taxonomic groups of the family. Thus the development of xeromorphic adaptations in the crane-flies larvae proceeds in a full accordance with the law of homologous series. In the cycles of T. leucoprocta and T. kashkarovi development a high-altitude gradient is outlined. Their development, which is monovoltine in the middle zone of the mountains with the increase of the inhabitance absolute level becomes probably hemi-voltine, at first facultatively and then obligately (T. kashkarovi). It occurs at great al-titudes owing to the life-time prolongation from one to two years of the larvae of both types and their repeated hibernation in the larva phase.